The addition of blood flow restriction to resistance exercise in individuals with knee pain: a systematic review and meta-analysis - Cuyul Vásquez, Iván.; Leiva Sepúlveda, Alejandro.; Catalán Medalla, Oscar.; Araya Quintanilla, Felipe.; Gutiérrez Espinoza, Héctor J. (Elsevier, 2020)
Background: Blood flow restriction (BFR) is an effective clinical intervention used to increase strength in healthy individuals. However, its effects on pain and function in individuals with knee pain are unknown. Objective: To determine the effectiveness of adding BFR to resistance exercise for pain relief and improvement of function in patients with knee pain. Methods: Systematic review with meta-analysis of randomized clinical trials. Medline, Central, Embase, PEDro, Lilacs, CINAHL, SPORTDiscus, and Web of Science databases were searched from inception to May 2019. Randomized clinical trials that compared resistance exercise with or without BFR to treat knee pain and function in individuals older than 18 years of age with knee pain were included. Results: Eight randomized clinical trials met the eligibility criteria and for the quantitative synthesis, five studies were included. The pooled standardized mean difference (SMD) estimate showed that resistance exercises with BFR was not more effective than resistance exercises for reducing pain (SMD: −0.37 cm, 95% CI = −0.93, 0.19) and improving knee function (SMD = −0.23 points, 95% CI = −0.71, 0.26) in patients with knee pain. Conclusion: In the short term, there is low quality of evidence that resistance exercise with BFR does not provide significant differences in pain relief and knee function compared to resistance exercises in patients with knee pain.
Keywords: Anterior knee pain; Blood flow restriction; Knee; Osteoarthritis; Systematic review